STRATEGI PEMASARAN DALAM UPAYA PENINGKATAN HUNIAN KAMAR PADA SENSE SUNSET SEMINYAK HOTEL - Ni Nyoman Menuh; Ni Wayan Widiantari (Warmadewa Management and Business Journal (WMBJ), 2021)
The increasing number of tourists coming to Bali will also affect the development of tourism facilities such as accommodation facilities and other supporting facilities. This study aimed to understand the Sense Sunset Seminyak Hotel's strengths and weaknesses in conducting its marketing activities and find out the marketing strategy used to improve the room occupancy rate in the Sense Sunset Seminyak Hotel. Data collection methods used were observation, interview, documentation, and questionnaire. The data analysis techniques used were the EFAS, IFAS and SWOT Analysis. The study result states that the Sense Sunset Seminyak Hotel position is in the quadrant I, i.e., the Growth strategy or vertical integration strategy. The SWOT analysis found several marketing strategy alternatives in improving the occupancy, which consists of the SO Strategy: enhancement in advertisement intensity and the creation of the business hotel, the WO Strategy: the creation of press relationship and scheduling of personal selling, the ST Strategy: reinforcement of brand image, and the WT Strategy: improvement of public relation role in facing the global economy.